(untitled) (Siddhajyoti Interdisciplinary Journal, 2024)
This article attempts to explore the causativized syntactic complex predicates in the southern Saptarian Maithili analysing them within Lexical Functional Grammar (LFG) and also pinpoint show English teachers/learners with Maithili background are facing difficulties for expressing such concepts in English. The data were mostly based on the researcher’s own PhD work, his own intuition and experiences and also from the secondary level students/teachers, and presented them using Leipzing glossing rules analyzing under the four interacting structures of LFG. It is found that this variety uses the predicative item lǝga ’cause/force’ with another predicative polar to form the causative syntactic complex predicates and such a construction is causing problems for the students learning English. Thus, English teachers in particular area to be conscious about the students’ difficulties in learning English, especially while dealing with the concepts of Maithili complex predicates.